DAMPAK PEMBELAJARAN DALAM JARINGAN (DARING) TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA DINI - Putri Bungsu; Sari Dewi (Early Childhood: Jurnal Pendidikan, 2021)
The objective of this study were to find out implementation and impact of online learning at Kindergarten Kemala Bhayangkari 01 Padang and know how gross motor develop during online learning. This research uses descriptive qualitatif method. Data collected by using interview, observation, and documentation in order to obtain accurate results. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. Data validity technique using triangulation technique. Based on the results of research conducted at Kindergarten Kemala Bhayangkari 01 Padang, it can be concluded that the implementation of online learning is in accordance with applicable educational standards but has a negative impact on child’s gross motor development because of the lack of learning assistance by parents. The fact shows from the fifteen children, only seven children who do the task during learning online while the other eight children did not collect assignments. Keywords : Online Learning, Impact of Online Learning, Motor Development.